Strategies for Sustainability in Post-COVID-19 Era: Insights from Selected Hotels - Danso Bertha Ada,; Fenteng Rita Adasi,; Amadu Wilhelmina Aisha,; Agyapong Awuradwoa Nyarkoa, (African Scientific Journal, 2025)
Abstract The post-COVID-19 era has transformed the hospitality industry, emphasising the need for resilience, sustainability, and innovation. This study analyses the factors influencing hotel sales and the strategies employed to maintain operations in the post-pandemic period. Using a mixed-methods approach, structured interviews were conducted with nine participants who were purposively sampled from hotels across three different star ratings. Demographic data were analysed with Microsoft Excel Professional Plus 2019, while the interview responses were analysed thematically. The findings indicate that the pandemic had a significant impact on employment, customer patronage, and sales performance. Many hotel staff displaced during the pandemic still face limited job options, while customer patronage, though improving, remains below pre-pandemic levels. Sales performance is moderate, showing partial recovery but no growth. To address these issues, the study recommends that hotel managers diversify revenue streams, strengthen their digital presence, adopt technological innovations, and implement sustainable practices. These strategies are essential for building resilience, maintaining competitiveness, and ensuring long-term sustainability in the evolving hospitality sector. Keywords Hospitality industry, post-COVID-19 pandemic, sales performance, sustainability, thematic analysis